Pembuatan, Pelatihan Perawatan, dan Perbaikan Panel Surya Cell di Proklim Karangmojo Weru Sukoharjo - Onery Andy Saputra; Nurma Puspitasari; Sudiro Sudiro; Riksi Irnawan; Ezra Putra Mulia; Galang Ilham Ramadan (Universitas Muhammadiyah Semarang, 2023)
Development of climate change within the community to increase public awareness about climate change which is increasingly real. The government, through the pro-climate competition, hopes that there will be more understanding and awareness to save the environment. In the proklim competition, it is necessary to have environmentally friendly technology, one of which is a solar cell. Polytechnic Indonusa Surakarta through the MBKM program. Students conduct training, maintenance, and repair of solar cell panels at Proklim Karangmojo Weru Sukoharjo. This is done so that the Karangmojo Proklim won the championship at the national level proklim competition while at the same time increasing public awareness of climate change and also increasing public knowledge about solar cell technology. The method used is a survey, planning, manufacturing, maintenance, and repair of solar panels. The results obtained are solar panels installed properly and running according to plan.